2023
DOI: 10.1002/jmv.28559
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of memory B cells and circulating T follicular helper cells is a predictor of poor immune recovery in HIV‐infected patients on antiretroviral therapy

Abstract: T follicular helper (Tfh) cells and their interactions with B cells within the germinal center play extensive roles in human immunodeficiency virus (HIV) pathology. However, their association with immune reconstitution during antiretroviral therapy (ART) is still unclear. The aim of this study was to determine the impact of Tfh and memory B cell function on T helper cell recovery in patients with acute or chronic HIV infection. A total of 100 HIV-infected individuals were enrolled in our study, classified into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…In HIV infection, B cell-mediated immune response is sustained by HIV-specific memory B cells and plasma cells ( 148 ). A recent study found that the proportions of naïve B, memory B, and plasma cells are not associated with immune recovery, while the low frequency of CD21 + memory B cells is a risk factor for incomplete immune reconstitution ( 149 ). This may be related to the dysregulation of memory B cells and circulating T follicular helper cells ( 149 , 150 ).…”
Section: Other Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In HIV infection, B cell-mediated immune response is sustained by HIV-specific memory B cells and plasma cells ( 148 ). A recent study found that the proportions of naïve B, memory B, and plasma cells are not associated with immune recovery, while the low frequency of CD21 + memory B cells is a risk factor for incomplete immune reconstitution ( 149 ). This may be related to the dysregulation of memory B cells and circulating T follicular helper cells ( 149 , 150 ).…”
Section: Other Immune Cellsmentioning
confidence: 99%
“…A recent study found that the proportions of naïve B, memory B, and plasma cells are not associated with immune recovery, while the low frequency of CD21 + memory B cells is a risk factor for incomplete immune reconstitution ( 149 ). This may be related to the dysregulation of memory B cells and circulating T follicular helper cells ( 149 , 150 ). In addition, another study found that the diversity of the B-cell receptor repertoire in HIV-INRs was decreased, and naïve B cells with low differentiation improve the immune reconstitution ( 151 ).…”
Section: Other Immune Cellsmentioning
confidence: 99%
“…Moreover, a recent study analyzing the baseline proteome of B cells from patients with acute HIV infection showed approximately 2500 significant proteins differentiated among groups. Specifically, the TGF-β, NF-κB and CD35 proteins were highly altered in INR compared to IR and healthy controls ( Table 1 ) ( 44 ). The enormous number of altered proteins found in this study suggests that dysregulation of B cells in HIV patients may serve as a predictor of poor CD4 + T-cell recovery.…”
Section: Proteomics: the Means To Execute The Inr Blueprintmentioning
confidence: 99%
“…Accordingly, it has been shown that IL-2, IL-4, IL-10, IL-17, and IFN-γ levels are significantly lower in INR than in IR ( 15 , 85 ). These cytokines are strongly involved in T-cell activation and proliferation, and their decrease might lead to their depletion ( 43 , 44 , 83 ). Interestingly, Meyer et al.…”
Section: Proteomics: the Means To Execute The Inr Blueprintmentioning
confidence: 99%
See 1 more Smart Citation